Examen especial a la cuenta cartera de microcrédito por vencer de la Cooperativa de Ahorro y Crédito Jardín Azuayo Ltda., de la ciudad de Loja, periodo 2022. - Armijos Suquilanda, Edinson Randol (2024)
This curricular integration project has been developed with the purpose of fulfilling a requirement established by the National University of Loja, in accordance with the provisions of the Academic Regime Regulations to obtain the title of Bachelor in Accounting and Auditing. The application of the special examination fulfilled the proposed objectives, such as evaluating internal control and determining the reasonableness of the balances that make up the overdue microcredit portfolio of Cooperativa de Ahorro y Crédito Jardín Azuayo Ltda. Additionally, it aimed to prepare a special examination report to facilitate informed decision-making. The methodology used was based on the phases of the Special Examination. In the first stage, planning, a preliminary and specific planning memorandum was prepared; in the second phase, execution, audit programs were developed and applied, and in the third phase, communication of results, a special examination report was drafted outlining the deficiencies in the internal control of each examined item. As a result of the Special Examination process, the following outcomes were obtained for the overdue microcredit portfolio: a risk level of 10.42% and a confidence level of 89.58%. This indicates that the cooperative's overdue microcredit portfolio has a moderate risk level of 10.42% and a confidence level of 89.58%. The main conclusion establishes that the overdue microcredit portfolio of Cooperativa de Ahorro y Crédito Jardín Azuayo Ltda. was evaluated concerning the implemented internal control system. Procedures were applied, revealing the control of operations and activities related to the overdue microcredit portfolio. It was determined that members have a low percentage of delays in payments with their debts and are in compliance with certain articles of the Internal General Regulations of the Cooperative and the Internal Tax Regime Law.